Desempenho clínico de um sistema de resina composta e adesivo silorano em restaurações de classe I - Carolina Dolabela Leal (2010)
Tensions generated by the polymerization shrinkage of composite resins can result in failure of restorations due to post-operative sensitivity, marginal gaps and secondary caries lesions. A silorane composite matrix was recently launched in the market, the main feature of the low polymerization shrinkage. This split-mouth clinical study compared the performance of composite resin FiltekTM P90 / P90 Adhesive System (3M-ESPE) with composite resin FiltekTM P60 / AdperTM SE Plus (3M-ESPE) in Class I occlusal restorations. Each individual (n = 35) received at least one pair of restorations, randomly allocated in the test group (P90) and control group (P60). A single operator carried out the preparations and restorations, using the materials in accordance with manufacturer's guidelines. A week later, the restorations were finished and polished and were evaluated blindly and independently by two trained examiners (kW 0.7). Three months after the restorations were evaluated again by the same two trained investigators blindly and independently (kW 0.84) using the modified United States Public Health Service criteria. Wilcoxon test compared the frequencies of scores Alpha, Bravo and Charlie in the test and control groups at baseline and after 3 months ( = 5%). At baseline and after 3 months, no statistically significant difference between groups regarding the criteria for marginal discoloration, marginal integrity, surface texture, anatomical form and postoperative sensitivity (p> 0.05). Within each group, the restorations did not differ between baseline and 3 months (p>0,05). It was concluded that during the period of initial evaluation, the clinical performance of silorane composite resin was similar to methacrylate resin.